Women’s Preferences for Advertised Chemical Products vs. Natural Herbal Ingredients for Reproductive Organ Hygiene and Health - Mauludiyah, Indah; Miftakhul Mahfirah Ermadona; Eva Inayatul faiza; Riski Akbarani (Babali Publisher, 2026)
Introduction: The comparison between advertised chemical-based products and natural herbal ingredients largely depends on individual preferences, cultural backgrounds, and personal experiences. This study aims to analyze the extent to which advertisements and other factors influence women of reproductive age's consumer preferences for chemical-based and herbal hygiene products.Methods: This study analyzed the preferences of women of reproductive age regarding reproductive hygiene products, comparing chemical-based products advertised with natural herbal alternatives. A quantitative survey was conducted on 100 women aged 15–45 years in Kepanjen, Blimbing, Singosari, and Dau, using a stratified random sampling method. Data were collected via questionnaires covering knowledge, product use, selection reasons, and satisfaction levels. Descriptive analysis and Chi-Square (χ²) tests were applied to examine relationships between information sources, product types, and satisfaction levels.Results: 70% of respondents used chemical-based products, mainly due to advertising (45%), while 35% prefered herbal products for safety and family tradition (60%). Respondents who obtained information from advertisements were more likely to use chemical-based products (χ² = 22.48, p = 0.0041), whereas those consulting healthcare professionals preferred herbal products (χ² = 15.72, p = 0.028). A significant relationship was found between product type and satisfaction level (χ² = 9.00, p = 0.0111), with users of herbal products reporting higher satisfaction. However, no significant association was found between product type and side effects (χ² = 5.63, p = 0.060), suggesting that other factors may influence side effects.Conclusion: Although most women prefer chemical-based products due to advertising, satisfaction levels are higher among users of herbal products. Further education on the benefits and risks of both types of products is essential to help women make informed choices for maintaining reproductive hygiene and health.